Efektivitas Pelayanan Pengurusan Paspor Berbasis Online Di Kantor Imigrasi Kelas I TPI Bengkulu - Nopa Sintia; Harius Eko Saputra; Maryaningsih Maryaningsih (Universitas Dehasen Bengkulu, 2024)
This study aims to determine the effectiveness of online-based passport administration services at Class I Immigration Office of TPI Bengkulu. The study uses a qualitative descriptive method. Data collection techniques include interviews, observation, and documentation. After obtaining the research results, data analysis is performed through data reduction, data presentation, and drawing conclusions. The informants in this study consist of five (5) individuals, including one (1) key informant and four (4) main informants. The study utilizes the theory by Hassel Nogi Tangkillisan (2005: 140-141), with the following indicators: (1) Target Achievement: the success rate of the program and the efficiency of resource utilization, the waiting time for passport issuance measured in days or hours. Regular passport estimation takes three days while expedited passports are issued in a day. (2) Adaptation Ability: this indicator measures how well employees and the public understand and possess the skills to use technology. (3) Job Satisfaction: ease of use regarding how easily the public feels using the online passport service system. This includes navigation, clear instructions, and a simple application process. (4) Responsibility: applicants are responsible for understanding passport application requirements before registering, required documents, personal information needed, application steps to be followed, and payment of fees.